Evaluation of Thyroid Dysfunction in Adult Patients of Celiac Disease - Nauman Wazir; Shafqat Ur Rehman (Gandhara University, 2021)
OBJECTIVES: To assess free thyroxine (fT4), thyroid stimulating hormone (TSH), and anti thyroid peroxidase antibodies (anti TPO abs) in adult Celiac disease patients and non-celiac controls and to find out any statistically significant difference in their corresponding means between the two groups. METHODOLOGY: The study design was analytical cross sectional. Sixty adult patients of celiac disease (CD) and 30 apparently healthy non-celiac adults were included in the study. CD patients had earlier been diagnosed by elevated levels of serological evidence of elevated (greater than 15X ULN) anti tissue transglutaminase (TTG) (IgA class) antibodies. CD was ruled out in the control group by normal levels of the antibodies. TSH, fT4 and anti TPO abs were obtained from all individuals of CD patient and control groups. RESULTS: Mean age of Celiac disease in patients was 23.85±5.43 years. Mean age of individuals in the control group was 24.26±5.55 years. Statistically significant difference in mean TSH and anti-TPO abs levels between the CD patient group and control group (p values of 0.03 and 0.038, respectively) was present. No statistically significant difference was seen between mean fT4 of patients and control group (p=0.74). Subclinical and overt hypothyroidism was present in 10% and 5% of CD patients, while anti TPO abs was positive in 16.6% of CD patients. CONCLUSION: There is a considerably high prevalence of subclinical and overt hypothyroidism as well as serological evidence of thyroid dysfunction in adult patients of CD.